Perancangan Animasi 3D Untuk Pertolongan Pertama Pada Kucing Berbasis Website - Alin Meisya Putri; Dahliyusmanto Dahliyusmanto; Dewi Nasien (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Cats are pets that are liked by people of all ages and circles, including in Indonesia. Adorable physical form and behavior are the reason cats are much liked. However, people's knowledge is currently lacking on care, health, and first aid for cats. Website-based 3D animation is a good place to convey information about health and give first aid to cats. In this study, 3D animation was created using Blender software. 3D animation videos hosted on the website. The website used in this study uses a static website type. The programming languages used in making this website are HyperText Markup Language (HTML), JavaScript, and Cascading Style Sheet (CSS). The complete address of the website results is p3k-kucing.nunitostudio.com. 3D animation videos and websites were tested for usability using a Likert scale. The test was conducted on 20 respondents from various circles and one validator, namely a veterinarian. The test results show that this website-based 3D animation is in the very worthy category.Keywords: Cats, 3D Animation, Website